Restrukturisasi MAK : Studi Kebijakan Penyelenggaraan Program Tafaqquh fid-Din Era UU Sisdiknas No 20 Tahun 2003 - Suwendi Suwendi (Badan Litbang dan Diklat Kementerian Agama RI, 2006)
Implementation of national education system law number 20 year 2003 apparently brings out new problem. some articles arranging the kinds of education, educational management, and majors (articles number 15, 18, 30) do not give a clear explanation or direction of what, where, and how the legal status of Madrasah Aliyah Keagamaan (MAK). The problematic’ implication of the unclarity of such legal messages is that the madrasah stake-holders not only confused in understanding the status or position of the MAK, but also the status of MAK institution itself becomes very problematic. the article tries to describe the real condition of MAK today including the problems faced by madrasah itself, the real needs and public aspiration toward the existence of MAK, and also the management of tafaqquh fiddin programs of MAK in the future.